The Integrative Conflict Mapping: A Strategic Instrument Towards Conflict Responsive Area - Suparman Abdullah; Suryanto Suryanto; Hariashari Rahim (Department of Sociology Faculty of Social and Political Sciences, 2019)
The most important of this study is to form an integrative instrument of conflict mapping towards conflict responsive area. It is the main benefit of the objectives of study that to gain a brief description of conflict potentials in local area and to propose a strategic model of local conflict responsive based on social capital. The method use is mixed method: quantitative-qualitative. Data collected by questioner and in-depth interview during May to June 2016. The results of the study are; the strategic instrument towards conflict responsive area is integrative conflict mapping between conflict analysis and social capital potentials; there are 122 conflict potentials along May 2013 to May 2016, and the major conflict potential is natural and environmental resources issue. The second is economic resources. Ethnic and religion, then politics and territory is the next conflict potentials. This study proofs that conflict potentials could be prevent, manage and find resolution by profiling data through the implementation of integrative conflict mapping.